2015 IEEE/AIAA 34th Digital Avionics Systems Conference (DASC) 2015
DOI: 10.1109/dasc.2015.7311372
|View full text |Cite
|
Sign up to set email alerts
|

Method to emulate the L-band digital aeronautical communication system for SESAR evaluation and verification

Abstract: The VHF voice communication system currently used for air traffic control is experiencing increasing capacity problems. The "L-band Digital Aeronautical Communications System" is an upcoming technology providing an aeronautical datalink outside of the VHF band. The objective of this paper is to develop a method to emulate its communication performance. We developed a formal model of the system and implemented it on the basis of the dummynet network emulation tools. This implementation was deployed in a network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…It allows for rapid prototyping of aeronautical communications systems via powerful tools, allowing for the simulation of real air traffic and air traffic data patterns, as well as the simulation of the data links responsible transmitting that data. LDACS emulations [62], as well as actual LDACS flight trials in 2019 [5] confirmed the correctness and precision of the LDACS implementation within FACTS2.…”
Section: B Computer Simulationsupporting
confidence: 55%
“…It allows for rapid prototyping of aeronautical communications systems via powerful tools, allowing for the simulation of real air traffic and air traffic data patterns, as well as the simulation of the data links responsible transmitting that data. LDACS emulations [62], as well as actual LDACS flight trials in 2019 [5] confirmed the correctness and precision of the LDACS implementation within FACTS2.…”
Section: B Computer Simulationsupporting
confidence: 55%
“…In 2015, Gräupl et al [27] presented a full methodology on how to emulate latencies for user data in the forward and reverse link of LDACS depending on the Bit Error Rate (BER) and message size. The required equations to calculate FL/RL latencies for LDACS are briefly described in the following and for more details of LDACS framing, we refer to [8].…”
Section: B Model To Emulate Latencies For Ldacsmentioning
confidence: 99%
“…Further we checked for different BERs, to measure the impact of the BER on performance. BER steps were chosen according to previous work [14], ranging from 0, 10 −6 , 10 −5 and10 −4 . However the BER should only start to be noticeable around a BER of 10 −5 .…”
Section: A Time Overhead By Security Additionsmentioning
confidence: 99%